(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A largely accepted enunciation to describe humanism as the supremacy of the spirit of man and the high ideals of justice and equity imbued with compassion, from all angles and in all walks of life. Today our society and the world have to remind themselves that the spirit of humanism which suffuses and radiates from Nehru’s writings and speeches not only provides the healing touch but also paves the path constructively for peace, harmony and civilizational progress to which humanity aspires. Nehru was not a religious man in the ordinary sense, but was imbued with a profound love for and belief in the people of India, and indeed of the world. What he called secularism was in fact a combination of humanism and pluralism. “Human values through human self – reliance”. Nehru’s humanism brings out both these elements quite eloquently – his passionate empathy with the toiling masses of India, his advocacy of peace for the war and violence torn humanity in the world and his clear rejection of reliance on supra-human or supernatural powers or beliefs for pursuing any goals.